Applied theories in occupational therapy : a practical approach - Cole, Marilyn B., 1945-; Tufano, Roseanna (Thorofare, NJ : SLACK Incorporated, 2020)
In this edition, we describe four levels of theory that incorporate most of the profession's knowledge base, as well as the broad external health care models within which we practice, teach, and conduct research. They are as follows: Broad models of health and wellness (medical, public health, client-centered, recovery) Professional paradigm (occupation focused, holistic, client centered, and complex systems oriented) based upon the occupational therapy philosophy, ethics, professional position papers, and guidelines from the OTPF3 (AOTA, 2014) Preface to the Second Edition Occupation-based models (addressing the complex interactions among person, environment, and occupation that enable occupational performance and participation) Frames of reference (tools for occupational therapists to guide assessment and intervention with specific disability areas that represent barriers to clients' meeting their occupational goals) These levels are presented according to their broadness of focus. The broadest are the health and wellness models, which are shaped by national and global trends within political, economic, social, and cultural systems. We focus on how occupational therapy theory has evolved and the way these larger systems have interacted and influenced our profession. We then look at how our profession's leaders describe various dimensions of the new paradigm of occupation, incorporating the complex, dynamic, and nonlinear systems theories that have generated the epistemological shift to multidimensional professional reasoning and contextual knowing"--
Includes bibliographical references and index.
Keywords: Arbetsterapi; Occupational therapy -- Philosophy; Occupational Therapy; Occupational Health; Models, Theoretical; Occupational therapy -- Philosophy; Occupational therapy